2022
DOI: 10.1002/batt.202200222
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Lithium Peroxide Growth Kinetically Driven by MoS2/MoN Heterostructures Towards High‐Performance Li−O2 Batteries

Abstract: The morphological control and spatial accommodation of Li 2 O 2 discharge products on the oxygen cathode are crucial to bolstering both the Coulombic and round-trip efficiencies of LiÀ O 2 batteries. Herein, MoS 2 /MoN heterostructures are constructed on carbon cloth to serve as the freestanding and binder-free oxygen cathode for LiÀ O 2 batteries, lending a low charge/discharge polarization of 0.79 V, a large specific capacity of 9.04 mAh cm À 2 , and a superb cycling stability beyond 800 h. Through comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In such situation, lithium‐oxygen batteries typically achieve a larger discharge capacity [7] . However, the wide band gap of Li 2 O 2 will set great obstacle for the charging process, leading to high charge polarization [5b,8] . Thus, finding an effective way to regulate the growth of Li 2 O 2 is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…In such situation, lithium‐oxygen batteries typically achieve a larger discharge capacity [7] . However, the wide band gap of Li 2 O 2 will set great obstacle for the charging process, leading to high charge polarization [5b,8] . Thus, finding an effective way to regulate the growth of Li 2 O 2 is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…The ever-escalating environmental and energy crises around the globe have put forward the research and development of advanced energy storage devices as a high priority. Rechargeable Li–O 2 batteries (LOBs), owing to the high theoretical energy density of 3505 Wh kg –1 and exploitation of inexhaustible oxygen as the cathode active material, have attracted particular interests among battery researchers. However, the deployment of the LOB technology is still in its infancy, with some critical challenges still to be dealt with, including the low round-trip energy efficiency caused by large charge/discharge polarization, the hazardous side reactions caused by high charging potential, and the accumulative deposition of insulative Li 2 O 2 and Li 2 CO 3 products that impede both charge and mass transfer. In order to address these issues, several strategic solutions have been proposed and implemented at both the material and device levels. These include the fabrication of highly efficient oxygen cathode catalysts (e.g., carbon materials, noble metals, metal organic frameworks, and heterostructured electrocatalysts) to kinetically expedite both the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), the supplement of redox mediators (e.g., I – /I 3 – , , TEMPO , ) into the electrolyte to lower both the thermodynamic and kinetic barriers of internal charge transfer, as well as the application of external fields (e.g., photovoltaic, electromagnetic) to complement the electric energy with other energy formats. In this context, the development of highly efficient field-sensitive catalysts with both enhanced ORR and OER activities is pivotal to advance the field-assisted LOB technology.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies have shown that converting Li 2 CO 3 into Li 2 C 2 O 4 might be a viable solution to circumvent its high decomposition barrier. , Wang and co-workers found that Mo 2 C could efficiently convert the inert Li 2 CO 3 into labile intermediate product Li 2 C 2 O 4 through coordinative electron transfer and thus led to an enhanced performance of recharged Li-CO 2 batteries . In our previous studies, we have demonstrated that reducing the size of discharge products by increasing the nucleation sites and/or charge kinetics also benefits their reversible decomposition in lithium-gas (such as Li-CO 2 and Li-O 2 ) batteries. Similar strategies to ameliorate the Li 2 CO 3 decomposition by modulating its morphology and crystallinity have also been reported. , Despite the considerable cycle performance of Li-CO 2 batteries demonstrated by these studies, they are mostly attained at a low depth of charge/discharge with the cycling capacity ≤1 Ah g –1 . This is because when the cycling capacity increases, the cyclic Li 2 CO 3 accumulation on the cathode surface becomes excessive and eventually leads to catalyst deactivation and redox shutdown.…”
Section: Introductionmentioning
confidence: 99%